DEPENDENCE OF POLITICAL LEADERS' OFFICIAL PHOTOS ON THE FORM OF GOVERNMENT IN THE WESTERN WORLD ( 1821-2013 ) - Vejvodová, Veronika (2016)
I study the role that facial expressions play in determining political ideology. I have collected 20,475 assessments of politicians representing 14 countries. Based on a dataset captured from 1821-2015, our results imply that the facial expressions of politicians do play a significant role in the explanation of their ideology. Controlling for positivism of expressions model confirms this general picture: Democratic regime politicians have a tendency to express positive emotions since they are in principle selling the future. Autocratic regimes are mostly trying to exert fear and the facial expressions of dictators are non-positive. We also find that evaluation of the regime is negatively correlated with TV broadcasting in some countries. Accordingly, we can claim that voting perception and behavior is guided by the pictures and videos which are delivered via television.